Faktor Yang Berhubungan Dengan Motivasi Kerja Pegawai Di Puskesmas Kairatu - Epi Dusra (Jurnal Rumpun Ilmu Kesehatan, 2021)
Motivation is the driving factor to achieve a quality services, especially in health. Work motivation is desirable in order to improve public health, it also can be expected to produce socially optimal production in accordance with the goals and ideals of the organization in the future. Research Purposes to determine the influence of work motivation on employee performance at Puskesmas Kairatu Method. This type of research used in this study was cross sectional. This research was conducted at the health center Kairatu West Seram regency. The population in this study were all employees of the health center Kairatu totaling 84 people. While the sample is done purposive sampling amounted to 69 people. The survey results revealed that respondents are less intensive relationship with the motivation to work as much (100%). For quite intensive relationship with the motivation does not support as many (10.8%) and motivational support as many (89.2%). known relationship with the working conditions are less motivation to work as much support categories (100%). For good working conditions to do with the motivation that does not support as many (11.4%) and support as many (88.6%). it is known that the relationship is less motivated colleagues support as many categories (100%). For a good relationship with co-workers motivation does not support as many (11.1%) sedangan motivational support as many (88.9%). Chi-square test results note that there is no significant relationship between the variables relationships with colleagues with the motivation which means p = 1.000 p> 0.05.